Scrub Typhus with Varied Clinical Presentations - Sarkar, Mihir; Banerjee, Susrita; Roychowdhuri, Satyabrata (Journal of Pediatric Infectious Diseases, 2018)
We present four cases of pediatric scrub typhus from a tertiary care center of eastern India, emphasizing on varied unusual clinical manifestations posing diagnostic difficulties. A low index of suspicion is required to prevent under diagnosis. We report a case series of four patients with scrub typhus having uncommon clinical manifestations (two patients with hemophagocytic lymphohistiocytosis, one patient with myocarditis, and one patient presenting with shock reminiscent of dengue shock syndrome). The response to doxycycline was good, with fever subsiding within 48 to 72 hours of starting the treatment. Three out of four cases completely recovered once appropriate medication was given.
Keywords: scrub typhus; hemophagocytic lymphohistiocytosis; myocarditis